Assessment of antibacterial, thrombolytic and cytotoxic potential of Cassia alata seed oil - Adnan Mannan, Md. Junaate Kawser, A. M. Abu Ahmed, Nazneen Naher Islam, S. M. Murshidul Alam, Mohammad Asif Emran Khan Emon and Shipan Das Gupta (Journal of Applied Pharmaceutical Science)
Cassia alata is a pan tropical shrub. It has been reported to have medicinal activities like laxative effect and active against ringworm, skin diseases and ulcer. The leaf extract of this plant has shown antibacterial activity. In this study, seed oil extracted from Cassia alata , was studied for Antibacterial, Thrombolytic and Cytotoxic activity by using in vitro techniques. Chloroform extract of the seed oil was tested for Antibacterial activity using disc diffusion method and that extract showed potent antibacterial activity against both Gram(+) and Gram(-) bacteria. DMSO extract of the seed oil was tested for Brine shrimp lethality bioassay using Brine shrimp nauplii. The LC50 of DMSO extract of Cassia alata seed oil was found to be 250Âµg/ml, indicates that the oil has moderate pharmacological action. The DMSO extract of the seed oil was also tested for in vitro thrombolytic activity. The extract showed reasonable thrombolytic activity against negative control (water).Further investigation on the plant is required to confirm their pharmacological activity and thereby utilizing them as useful medicinal plant.
Keywords: Cassia alata, Cytotoxicity, Oil, Thrombolytic, Streptokinase, Antibacterial